Practice Brokerage Services for the Sale and Purchase of Coffee from the Perspective of Syari'ah Economics - Maulana Iqbalwa (Islamic Research Publiser, 2022)
The purpose of this study is to find out how the practice of intermediary services for selling and buying coffee in Tanjung Aur Village, Maje District, Kaur Regency, and to find out how the Sharia Economic Law review is for the practice of intermediary services for buying and selling coffee in Tanjung Aur Village, Maje District, Kaur Regency. The type of research to be carried out is field research) using qualitative research. Informant determined with purposive sampling technique. Became informants in the study are coffee farmers and buying and selling brokers. The number of informants is 14 people. The study's results revealed that: (1) coffee intermediary services in Tanjung Aur Village were carried out between coffee farmers and buying and selling intermediaries. Farmers give power to intermediaries to sell the coffee they get to wholesalers or large buyers of agricultural products. After the coffee is sold, the farmer will receive the proceeds from the sale given by the intermediary. (2) Review of Sharia Economic Law on buying and selling coffee intermediary services in Tanjung Aur Village is illegal. As emphasized in the Al- Qur'an As-Syu'ara verse 183, which means do not harm humans in their rights and do not run rampant on earth by causing damage, and by the rules of fiqh, namely harm should be eliminated. So an act that can cause harm or loss between one party and another is not permissible